Antimicrobial Activity and Essential oil Compositions of Two Ranunculus Species from Turkey: R. constantinopolitanus and R. arvensis - TERZIOGLU, SALIH; YASAR, AHMET; YAYLI, NURAN; YILMAZ, NAGIHAN; KARAOGLU, SENGUL; YAYLI, NURETTIN (Asian Journal of Chemistry, 2010)
The isolated essential oils of Ranunculus constantinopolitanus and Ranunculus arvensis were tested for antimicrobial activity against the bacteria E. coli, K. pneumoniae, P. aeruginosa, E. faecalis, S. aureus, B. cereus and the fungus C. albicans. They showed moderate antimicrobial activity against P. aeruginosa, E. faecalis, S. aureus and C. albicans. The composition of essential oils obtained from the air-dried R. constantinopolitanus and R. arvensis were also analyzed by GC-MS. 45 and 36 Components were identified in the essential oils and the main component of these taxa was (Z)-phytol in the ratio 23.6 and 19.5 % from R. constantinopolitanus and R. arvensis, respectively.